On the Doctrinal Principles of Property Restitution - Spasybo, Illarion (Teisė, 2022)
This article aims to establish the reasons and demonstrate the necessity for restitution and its basic beginnings in Ukraine. The article emphasizes that process of restitution, which is undoubtedly needed in Ukraine, should be conducted in accordance to the principle of fairness in order to prevent a violation of private property rights.